Magnetic fabric of Siwalik sediments (Nepal): implications to time-space evolution of stress field - Gautam, Pitambar (Journal of Nepal Geological Society, 2008)
Magnetic fabric data based on the anisotropy of magnetic susceptibility (AMS) of the sediments constituting the Siwalik sections (Kamali R., Amilia- Tui Road, Surai R., Tinau R., and Rato R.) in Nepal have been analysed for the variability of magnetic lineation and the implications to the time-space evolution of the stress field in this region during the last 16 myrs. This invo lved compilation of (i) the magnetic polarity data that constrain the depositional age of the Nepalese Siwaliks to ca. 16 to 1 Ma, and (ii) the declination of characteristic magnetic remanence to reveal the relative tectonic rotations (17° CCW at Butwal to 9° CW at Amilia). The magnetic fabric, defined mainly by alignment of paramagnetic minerals, corresponds to an oblate ellipsoid with foliation parallel to bedding plane, implying a sedimentary-compactional origin. The magnetic lineations show well defined clusters (confined in or close to the bedding plane). Being subparallel to the fold axes/bedding strikes/thrust fronts, these lineations are assumed to originate from a secondary mild deformation process related to the compression tectonics in the Siwalik foredeep and therefore correspond to the active direction of the minimum principal horizontal stress active during foredeep deposition. Hence, the direction of compression is orthogonal to the mean lineation. The compression direction in the palaeogeographic coordinates can be obtained by introducing an additional correction for the tectonic rotation about the vertical, using the palaeomagnetic declination. Available AMS-based lineations, corrected for rotation about vertical using palaeomagnetic declinations, reveal that the compression direction in the Himalayan foreland remained in general N to NNE with significant deviations in its far western part, in particular around the Amilia- Tui section where the direction was NS8°E.